An ontology based approach to data surveillance - Pereira, Teresa (2008)
Nowadays the terrorist threat took proportions that concern governments and the national security organizations, all over the world. A successful terrorist incident usually brings catastrophic results. However if a terrorist attack can be predicted and characterized, it may be possible to organize a proper intervention in order to avoid it or to reduce its impact. The management of information is becoming an important issue in the domain of security information systems. The information access and association, analysis and assessment, and finally exploitation have become the focus for all security information services and governments. Current surveillance approaches are not very efficient leading innocent citizen to the confrontation of law enforcement services. One reason for this, result from the difficulties of the current system to extract knowledge or concepts abstracted from massive databases of information. Knowledge based methods, such as ontologies can integrate data surveillance, and enable a proper data analyse improving the performance of the security information services. This paper intends to present a perspective about the use of ontologies in the context of data surveillance, and present its importance in the current security services domain.